Job rotation in management at Automobili Lamborghini and Audi Hungary - Gubicza, Gábor; Remsei, Sándor (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2023)
This research has two main aims: First, to establish how sense-making/meaning-making facilitates job rotation success, and second, to determine whether there is a universally acceptable rotation interval for automotive management. This paper intends to examine and explore both research objectives and help to understand the management rotation phenomenon. Moreover, the researchers have collected and analyzed negative experiences (e.g., loss of specialized skills, decrease in productivity, or stress and anxiety) and ways of learning from them. Ideally, this research will lead to a better understanding of the job rotation process and better HR models and plans for job rotation. The researchers provided questionnaires about job rotation to staff at Automobili Lamborghini and Audi Hungary, with the survey paying particular attention to the second research question. Based on their research, the authors have not found an optimal rotation interval, but the questionnaire results suggest that this number is between three and six years. The research also provides detailed information on the average rotation time at two companies and a thorough analysis of the background and different aspects of managerial job rotation.